Protocol for a randomized controlled trial of an internet-based prevention intervention for young children at-risk for functional abdominal pain - Rona L. Levy; Tasha B. Murphy; Miranda A. L. van Tilburg; Margaret R. Kuklinski; Jennifer A. Bailey; Homer Aalfs; Isabel Badillo; Hafsah Diakhate; Tonya M. Palermo (Trials, 2024)
Abstract Background Chronic pain often clusters in families, where parents and their offspring both experience chronic pain conditions. Young children of parents with irritable bowel syndrome (IBS) represent an at-risk group for the development of abdominal pain, disability, and excess health care visits in later childhood. Parental solicitous responses to children’s expressions of discomfort and maternal modeling of their own illness behavior contribute to a greater focus on somatic sensations, leading to illness behaviors in children. This randomized controlled trial will test the effectiveness of an early preventive web-based psychosocial intervention (REACH)[TM] vs. an educational web-based safety comparison condition delivered to parents with IBS to alter parental responses and lead to improved child health and decreased health care costs. Methods Parents with IBS who have children ages 4–7 years are recruited via community-based approaches (e.g., social media advertisements, school electronic distribution, research networks) and health care providers. The target sample is 460 parents randomized to REACH, a web-based social learning and cognitive behavior therapy (SLCBT) intervention or an educational web-based safety comparison condition (EC). Participants will be assessed at baseline, 6-week (immediate post-intervention), 6-month, 12-month, and 18-month follow-up periods (months post-completion of intervention). The primary outcome is change in parental solicitous/protective behaviors. Secondary outcomes include parent risk and protective factors, child health and symptom outcomes, and health care utilization and cost savings. Discussion This study adapts a validated, parent-delivered intervention to treat chronic pain in children to a web-based application designed to prevent the development of chronic pain in very young, high-risk children. If successful, this strategy can both prevent adverse sequelae of this condition from developing as well as be widely accessible. Furthermore, the availability of a prevention model for parent training could result in significant short- and long-term health benefits across a broad spectrum of conditions. Trial registration ClinicalTrials.gov NCT05730491. Registered on February 15, 2023.